2021
DOI: 10.1212/wnl.0000000000011892
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Socioeconomic Status and Stroke Incidence

Abstract: ObjectiveTo summarize overall patterns of the impact of neighborhood socioeconomic status (nSES) on incidence stroke and uncover potential gaps in the literature, we conducted a systematic review of studies examining the association between nSES and incident stroke, independent of individual socioeconomic status (SES).MethodsFour electronic databases and reference lists of included articles were searched, and corresponding authors were contacted to locate additional studies. A keyword search strategy included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…Other studies have identified social and economic neighborhood characteristics as factors that are important to health, including cardiovascular disease, stroke, and mortality ( Brown et al, 2011 ; Diez-Roux et al, 2001 ; Freedman et al, 2011 ; Pujades-Rodriguez et al, 2014 ; Smith et al, 1998 ; Steenland et al, 2004 ; Sundquist et al, 2004 ; Winkleby & Cubbin, 2003 ). Some studies revealed that residence in a socioeconomically disadvantaged neighborhood can increase risk of incident stroke ( Brown et al, 2011 ; Kim et al, 2021 ; Kleindorfer et al, 2006 ; Lisabeth et al, 2007 ), which varied by sex or race ( Brown et al, 2011 ; Grimaud et al, 2011 ; Hart et al, 2000 ; Lisabeth et al, 2007 ; Pujades-Rodriguez et al, 2014 ). Another study found that stroke incidence increased with a decrease in neighborhood socioeconomic score (nSES) ( Howard et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have identified social and economic neighborhood characteristics as factors that are important to health, including cardiovascular disease, stroke, and mortality ( Brown et al, 2011 ; Diez-Roux et al, 2001 ; Freedman et al, 2011 ; Pujades-Rodriguez et al, 2014 ; Smith et al, 1998 ; Steenland et al, 2004 ; Sundquist et al, 2004 ; Winkleby & Cubbin, 2003 ). Some studies revealed that residence in a socioeconomically disadvantaged neighborhood can increase risk of incident stroke ( Brown et al, 2011 ; Kim et al, 2021 ; Kleindorfer et al, 2006 ; Lisabeth et al, 2007 ), which varied by sex or race ( Brown et al, 2011 ; Grimaud et al, 2011 ; Hart et al, 2000 ; Lisabeth et al, 2007 ; Pujades-Rodriguez et al, 2014 ). Another study found that stroke incidence increased with a decrease in neighborhood socioeconomic score (nSES) ( Howard et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A model included the number of expected deaths as an offset term to adjust for the population size of each municipality. Moreover, in terms of municipality-level socioeconomic status variables, this study adopted; the ratio of people who completed college and university studies (%), the proportion of workers in primary industries (%), such as agriculture and fishing, the proportion of workers in secondary industries (%), such as manufacturing and construction, and the proportion of workers in tertiary industries (%), mainly services [14][15][16][17]. However, these socioeconomic values were impact of socioeconomic factors on stroke is a global challenge, and improving access to healthcare may reduce disparities in outcomes.…”
Section: Response and Explanatory Variablesmentioning
confidence: 99%
“…15 The level of deprivation in a geographical area, commonly termed neighborhood socioeconomic status (nSES), is a risk factor for general health and well-being. 16,17 However, findings concerning association between nSES and risk of dementia are inconsistent. [18][19][20][21] The aim of the present study was to investigate the associations between nSES and missed or delayed diagnosis of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…The level of deprivation in a geographical area, commonly termed neighborhood socioeconomic status (nSES), is a risk factor for general health and well‐being 16,17 . However, findings concerning association between nSES and risk of dementia are inconsistent 18–21 .…”
Section: Introductionmentioning
confidence: 99%